Cat scratch disease: What to do with the cat? - Avital Lily Okrent Smolar; Edward B. Breitschwerdt; Paul H. Phillips; Nancy J. Newman; Valérie Biousse (American Journal of Ophthalmology Case Reports, 2022)
Purpose: Cat scratch disease (CSD) frequently has ophthalmologic manifestations. The ophthalmologist's approach to treating neuroretinitis is familiar, but few eye care providers are comfortable answering the next question of “what do I do with my cat?” Published guidelines are often vague in answering the complexities of real-life conundrums that can lead patients and their doctors to believe that risk mitigation should involve removal of the animal. Here, we present demonstrative scenarios informed by clinical practice and provide updated recommendations. Observations: A 10-year-old boy presented with reduced vision in the right eye. Funduscopic examination identified optic nerve head edema with subretinal fluid, and a macular star developed one week later, consistent with the diagnosis of neuroretinitis. Serology confirmed Bartonella henselae antibodies and a diagnosis of CSD. The father disclosed that the family has recently adopted three kittens, who have scratched the boy and the patient's younger sister. The physician and patient's family find themselves at a loss regarding best practices for what should be done with the kittens. Conclusions and Importance: B. henselae has been detected in a variety of mammals and can be transmitted via vectors such as fleas. Even well-appearing animals can transmit the bacteria, months to years after their initial infection. Symptoms, clinical and laboratory findings will depend on bacterial load and strain virulence, as well as the physiological/immunological status of the host, with people at the extremes of age and the immunocompromised being at greater disease risk. Flea control is crucial to minimize transmission risk. Our veterinary expert (EBB) recommends testing (with serology and PCR) and treating infected animals (with doxycycline and a quinolone). Patients should be counseled to speak with their pets’ veterinarian. When addressing the concerns of our CSD patients in clinical practice, ophthalmologists should be aware of the strategies for minimizing Bartonella transmission risk, and cognizant of the One Health approach for managing zoonoses.